Fetal anemia - Huertas Tacchino, Erasmo (2015)
In fetal anemia hemoglobin (Hb) concentration is below 2 standard deviations or <0.84 MoM in relation to median Hb in the general population. Gold standard in diagnosis is measuring fetal Hb by percutaneous chordocentesis, but medial cerebral artery systolic velocity peak (MCA – SVP) would be the best test for non invasive diagnosis of fetal anemia. MCA – SVP levels equal or above 1.55 MoM for gestational age correlate with moderate to severe fetal anemia. It is important to emphasize that a trained operator is conditio sine qua non for the correct sampling of MCA - SVP. It is useful to remember that MCA- SVO measurement has a high 12% false positives increasing at 35 weeks and following blood transfusion.